Development And Evaluation Of Matrix Type Transdermal Patches Of Donepezil - Kamal Vachhal, Ishat; Nandi, Sisir (Journal of Neonatal Surgery, 2025)
The present study focuses on the formulation and evaluation of matrix-type transdermal drug delivery systems (TDDS) of Donepezil, a drug commonly used in the treatment of Alzheimer’s disease. TDDS offers numerous advantages over traditional drug delivery systems, including controlled release, improved patient compliance, and avoidance of first-pass metabolism. In this study, ten different transdermal patch formulations of Donepezil were developed using the solvent evaporation method with various combinations of polymers such as HPMC, ethyl cellulose, chitosan, and PVP K30. Preformulation studies, including melting point, solubility analysis, partition coefficient determination, and FTIR spectroscopy, were conducted to assess the drug’s physical and chemical properties and compatibility with selected excipients. The patches were characterized for physicochemical properties such as thickness, weight uniformity, folding endurance, moisture content, drug content, and water vapor transmission rate (WVTR). In-vitro drug release studies were conducted using Franz diffusion cells and UV spectroscopy, and release kinetics were evaluated. Among the formulations, patch P4 exhibited the highest drug release (71.28%) over 7 hours and was found to be stable under accelerated stability conditions. Release kinetics followed the Korsmeyer-Peppas model, indicating a diffusion-controlled mechanism. The study concludes that the matrix-type TDDS of Donepezil, especially formulation P4, demonstrates potential for sustained drug release and improved therapeutic efficacy in treating cognitive disorders.